Testbeam performance results of bent ALPIDE monolithic active pixel sensors in view of the ALICE inner tracking system 3 - Blidaru, Mihail-Bogdan (Journal of Instrumentation, 2022)
The ALICE Inner Tracking System has been recently upgraded to a full silicon detector consisting entirely of monolithic active pixel sensors, arranged in seven concentric layers around the LHC beam pipe. Further ahead, during the LHC Long Shutdown 3, the ALICE collaboration is planning to replace the three innermost layers of this new ITS with a novel vertex detector. The proposed design features wafer-scale, ultra-thin, truly cylindrical MAPS. The new sensors will be thinned down to 20-40 mu m, featuring a material budget of less than 0.05% x/X-0 per layer, unprecedented low, and will be arranged concentrically around the beam pipe, as close as 18 mm from the interaction point. Anticipating the first prototypes in the new 65 nm CMOS technology node, an active R&D programme is underway to test the response to bending of existing 50 mu m thick ALPIDE sensors. A number of such chips were successfully bent, even below the targeted innermost radius, without signs of mechanical damage, while retaining their full electrical functionality in laboratory tests. The curved detectors were subsequently tested during particle beam campaigns, where their particle detection performance was assessed. In this contribution, testbeam highlights from the data analysis of bent ALPIDE sensors, will be presented. It was proved that the current ALPIDE produced in the 180nm CMOS technology retains its properties after bending. The results show an inefficiency that is generally below 10(-4), independent of the inclination and position of the impinging beam with respect to the sensor surface. This encouraging outcome proves that the use of curved MAPS is an exciting possibility for future silicon detector designs, as not only the sensor can survive the bending exercise mechanically, but the enticing attributes that make it attractive for use in the inner tracking layers are comparable to the flat state.